BASIC HOPE AND EXISTENTIAL ANXIETY AMONG ADULTHOOD GENERATIONS - Gawda , Barbara (Psychological Prospects Journal, 2022)
Purpose. This study attempts to show the level of basic hope and existential anxiety among younger adults/emerging adulthood and middle adult generations. Basic hope is seen as a positive feeling playing a fundamental motivational role in the regulation of human behavior. It has been pointed out that hope is a prospective emotion that, contrary to fear/anxiety, is directed toward the future. Existential anxiety is thought to be inversely related with hope which means that existential anxiety is associated with unresolved intra-psychic conflicts.Methods. A sample of 139 younger and adult participants from the general population was examined. They represented three stages of adulthood: emerging adulthood (59), early adulthood (28), middle adulthood (52). They completed two self-measure questionnaires focused on basic hope (Basic Hope Inventory – 12 by Trzebiński and Zięba) and existential anxiety (Existential Anxiety Questionnaire by Weems and associates). Results. The results indicate that the younger generation/emerging adulthood displays a higher level of existential anxiety and lower level of basic hope than other adult generations. Young people who feel higher existential anxiety do not believe that their future will be positive. Adult women display a higher level of basic hope than men while the level of existential anxiety is similar in both women and men Conclusions. The results document developmental characteristics of the stage named emerging adulthood. At this stage of development, people are particularly vulnerable, full of fear for their future, they have to make important decisions about their education, professional decisions, and close interpersonal relationships. As their hope is low and existential anxiety is high they do not perceive their future positively.
Keywords: basic hope; existential anxiety, emerging adulthood, early and middle adulthood.